2012 12th IEEE-RAS International Conference on Humanoid Robots (Humanoids 2012) 2012
DOI: 10.1109/humanoids.2012.6651535
|View full text |Cite
|
Sign up to set email alerts
|

Gain-field modulation mechanism in multimodal networks for spatial perception

Abstract: Abstract-Seeing is not just done through the eyes, it involves the integration of other modalities such as auditory, proprioceptive and tactile information, to locate objets, persons and also the limbs. We hypothesize that the neural mechanism of gain-field modulation, which is found to process coordinate transform between modalities in the superior colliculus and in the parietal area, plays a key role to build such unified perceptual world. In experiments with a head-neck-eye's robot with a camera and microph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…However, this work does not address the problem of coordinate transformations between different modalities in multisensory integration. Previous works done by the authors model the mechanism of gain-modulation found in parietal neurons for audio-visual and visuomotor coordinate transformations4344. In future works, one attempt will be to extend this model to coordinate tranformation of visuo-tactile and proprioceptive reference frames for simulating RHI with a robotic hand.…”
Section: Discussionmentioning
confidence: 98%
“…However, this work does not address the problem of coordinate transformations between different modalities in multisensory integration. Previous works done by the authors model the mechanism of gain-modulation found in parietal neurons for audio-visual and visuomotor coordinate transformations4344. In future works, one attempt will be to extend this model to coordinate tranformation of visuo-tactile and proprioceptive reference frames for simulating RHI with a robotic hand.…”
Section: Discussionmentioning
confidence: 98%
“…In previous works, we demonstrated how the mechanism of gain-field modulation can be applied for integrating audio-visual signals and proprioceptive feedback in a head-neck-eyes robotic device as it is for some parietal neurons (Pitti, Blanchard, Cardinaux, & Gaussier, 2012). In our studies, the gain-field neurons were successfully used to remap the location of one sound signal (in head-centered reference frame) into retina coordinates (in eyecentered reference frame).…”
Section: Introductionmentioning
confidence: 83%
“…Their modeling corresponds to multiplicative Radial Basis Functions (RBFs) or sigma-pi networks [13], [14] to learn sensorimotor transformations. In image processing, these networks are known as gated networks, which have been recently re-investigated in [15], [16] for affine transformations and in developmental robotics [17], [18], [19] for multimodal integration. These multiplicative networks can serve to learn nonlinear transformations, which are common problems in robotics to compute direct mapping and inverse kinematics.…”
Section: Introductionmentioning
confidence: 99%